ANALISIS FRAMING MEDIA PEMBERITAAN PADA TRAGEDI KANJURUHAN MALANG:Studi Pemberitaan Detik.com, NarasiTV, Dan Tribunnews.com Periode 2 Oktober - 19 Oktober 2022 - Anshori, M Syukron; Rufaidah, Rufaidah; Suprapto, Deddy (Universitas Jember, 2023)
This research examines the framing of the Kanjuruhan Malang tragedy in online media outlets, specifically Detik.com, NarasiTV, and Tribunnews.com, utilizing Robert N. Entman's framing theory. The study employs four key elements of framing: problem definition, causal diagnosis, moral judgment, and treatment recommendations. The research methodology adopted is interpretative qualitative, employing Robert N. Entman's framing analysis. Data collection involved the compilation of news articles pertaining to the Kanjuruhan tragedy from the aforementioned online media sources. The findings of the research reveal that NarasiTV and Tribunnews.com, in their reporting, emphasize the use of tear gas, while Detik.com underscores allegations of falsehood and fraud involving the parties associated with the Kanjuruhan tragedy.